WEBINAR MENGEMAS HASIL PENELITIAN MENJADI ARTIKEL JURNAL ILMIAH UNTUK GURU KIMIA - Sonny Rohimat; Dwi Susilo; Iswarni Iswarni (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
One of the documents which are proofs a teacher's participation in online training or webinars is a certificate. When the Association of Indonesian Chemical Science Educators (PPSKI) in Banten Province held a webinar for chemistry teachers, the e-certificate of the activity could be received by each participant quickly and accurately. This very fast and accurate distribution of e-certificates uses the help of the Autocrat add-on on the Google Sheets attendance list. The steps taken in this activity are creating an e-certificate design; creating the attendance list format; creating Google Slides format; installing the Autocrat add-on; sharing the attendance list link. However, there were some participants who said that their e-certificates had not been received due to an error in filling in their email addresses or problems with the internet network.